Effect of CSR initiatives on a company's bottom line (Trinity Journal of Management, IT & Media (TJMITM), 2018)
Corporate social responsibility is one of the needful and  prominent business practices of today's scenario.  Companies Practising CSR has an enhanced overall  reputation and their corporate identity promotes positive  culture among society. The execution of a CSR process is  an important component of a company's assets and its  strategy is a competitive component in market itself which  is led by company itself. This means integrating 3P's which  acts a tool of society like people, planet and profit which  collaborates with(Internal and External Public)  stakeholders. Overall aim is to make a positive and strong  impact on society as a whole. The company's bottom line  refers to a company's net earnings, net profit or net income.  The term “bottom" explains the net income figure on a  company's income statement. Bottom line also refers to  any activity that may increase/decrease net earnings. A company that has more net earnings or reducing costs  cutting is said have “improving its bottom line". Most  companies aim to improve their bottom lines through two  simultaneous methods: growing profits through revenues  and increasing efficiency through cutting costs. This paper  focuses on how CSR initiative has affected the company  bottom line or overall growth. It will throw light on the  scenario and impact of CSR strategies followed by  companies. The purpose is well defined to know the 5w's  and 1H of CSR initiatives. With various case studies we will  try to answer who does CSR and how. What is the  company all about, where is it located, whom it is run by,  Since when it is running and how the company has  implemented CSR strategy and what was the result, This  paper has opted for descriptive research design. It is a  scientific method which involves observing and describing  the behavior of a subject without influencing it in any way.  Various research methods are implemented by  researches. Various case studies will be studied regarding  the implementation of CSR strategy by various companies  and how that has resulted and had an impact on society.  As we can see that this paper has used Descriptive  research design, or qualitative, various methods, include  the, case study, naturalistic observation, surveys, archival  research, longitudinal research, and cross-sectional  research. The Scope of the research is to know the  benefits of CSR schemes in India and to know whether  these CSR and philanthropy activities are useful in today's  scenario for people as well as company .
Keywords: Corporate Social responsibility; company's bottom line; people; profit; planet; Developed nation